Investigating Teacher Multitasking Practices and Their Implications for Student Learning - Alpisahri Panjaitan; Faisal Musa; Ainun Mardia Harahap (Al-Qalam Institue, 2025)
This study aims to analyze the forms of multitasking carried out by educators at SD Negeri 081 Panyabungan, its impact on the learning process, and the strategies used to manage multitasking. This research employed a qualitative phenomenological approach. Data were collected through observation, in-depth interviews, and documentation. The findings indicate that educators perform multiple tasks simultaneously and sequentially, including teaching, duty supervision, ceremony coaching, lesson plan evaluation, counseling, religious activities, Subuh prayer assistance, and extracurricular guidance. Multitasking provides benefits such as time efficiency and role flexibility but also poses challenges such as fatigue, stress, and decreased instructional focus. Therefore, managerial support and proportional task distribution are essential to maintain teaching quality.